Infección respiratoria en paciente infectado por VIH ¿COVID-19 o neumocistosis?: Reporte de Caso: Respiratory infection in an HIV-infected patient: COVID-19 or pneumocystosis?: Case report - Morales-Ibañez, Fátima (2023)
Opportunistic infections in immunocompromised HIV patients have for years been the main cause of mortality in this population, such as pneumonia caused by the fungus Pneumocystis jiroveci. SARS-CoV-2 infection is the cause of the COVID-19 pandemic. During this period, many patients who had a clinical similar to COVID-19 sought medical attention and that particular diagnosis was attributed to all of them. Given this situation, in many cases it was suspected that the patients had an infection by SARS-CoV-2, resulting in incorrect in-hospital treatment and measures. We present the case of an HIV-infected male who presented with pneumonia associated with probable COVID-19 or P. jirovecii infection. The aim of this case report is to establish the differences between SARS-CoV-2 and P. jirovecii pneumonia.